Jati Diri Melayu dan Multikulturalisme: Kontekstualisasi Jati Diri Melayu di Era Global - Rina Rehayati (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2013)
On the basis of Islamic values , philosophy of life developed by the Malay known earlier so wise, and seek to avoid conflicts exist with malaynese polite and understated. The success of the Malays formerly very strong with their identity needs to be transformed to the current generation. Therefore, efforts need to be examined to be done so that the glories of the Malay identity persisted, despite the world changing in any form.